Biological dose-escalated definitive radiation therapy in head and neck cancer - Costa Ferreira, Brigida (2021)
To compare treatment outcome of patients with head and neck (HN) tumours treated with definitive radiation therapy that, mainly owing to differences in the fractionation scheme used with simultaneous integrated boost techniques, resulted in a different biological dose.